Personal learning environment of the talented student - based on their own experiences - Kamińska, Aneta (Journal of Education Culture and Society, 2019)
Aim. The purpose of the research is to depict how talented students create their personal learning environment. The author of that paper shows a difference that has occurred thanks to the comparison between the manner in which average students and talented students build their personal learning environment.Methods. The author has conducted quantitative research, by making a survey. The surveys were carried out among fifty talented students. This paper focuses on the presentation of their opinions. The respondents presented how they constructed their personal learning environment. Additionally, they expressed their viewpoints about their digital competences.Results. The analysis shows that talented students are familiar with the latest digital tools. It allows them to design their personal learning space effectively. They can collect and process information profitably. They are also keen to share their knowledge with other participants of an educational process via the Internet, using some complex and practical devices. Moreover, talented students prefer discussing educational problems with other students online. They use some appropriate tools, such as chat rooms and social networking services. According to the research, the author can conclude that talented students are able to build and improve their digital learning space very well. They seem to create their personal learning environment functionally and consciously.Conclusions. Talented learners use advanced searching strategies, methods of collecting and storing information, and also teamwork tools. It is particular that they are autonomous learners but they also like sharing knowledge with other learners. The level of information competences of the talented students is quite high.